Approaches to Addressing Service Selection Ties in Ad Hoc Mobile Cloud Computing - Ayotuyi Tosin Akinola; Matthew Olusegun Adigun (Journal of Computer Networks and Communications)
The ad hoc mobile cloud (AMC) allows mobile devices to connect together through a wireless connection or any other means and send a request for web services from one to another within the mobile cloud. However, one of the major challenges in the AMC is the occurrence of dissatisfaction experienced by the users. This is because there are many services with similar functionalities but varying nonfunctional properties. Moreover, another resultant cause of user dissatisfaction being coupled with runtime redundancy is the attainment of similar quality computations during service selection, often referred to as “service selection ties.” In an attempt to address this challenge, service selection mechanisms for the AMC were developed in this work. This includes the use of selected quality of service properties coupled with user feedback data to determine the most suitable service. These mechanisms were evaluated using the experimental method. The evaluation of the mechanisms mainly focused on the metrics that evaluate the satisfaction of users' interest via the quantitative evaluation. The experiments affirmed that the use of the shortest distance can help to break selection ties between potential servicing nodes. Also, a continuous use of updated and unlimited range of users' assessments enhances an optimal service selection.